The links between sleep health domains and male/female obesity: a nationwide survey on the Iranian general population - Samaneh Akbarpour; Atefeh Behkar; Rahmatollah Moradzadeh; Zahra Banafsheh Alemohammad; Reihaneh Heidari; Amir Houshang Mehrparvar; Khosro Sadeghniiat-Haghighi; Arezu Najafi (Scientific Reports)
Abstract Studies examined one aspect of sleep health (sleep duration) as a risk factor for developing obesity. Approaching sleep health as a multidimensional model can better assess this association. This study investigated the role of gender in moderating the relationship between obesity and sleep health, adopting a multidimensional perspective on sleep health. This was a nationally representative cross-sectional survey using a multi-stage random clustering method. We included a cohort of 3198 individuals. We used STOP-BANG, Insomnia Severity Index, and self-report questions to define six sleep health domains: alertness, satisfaction, timing, efficiency, regularity, and duration. The Chi-square test evaluated the relationship between obesity and dichotomized sleep health dimensions. Logistic regression models determined the best predictors of obesity based on sleep health dimensions, adjusted for confounding factors. The mean age and body mass index of participants were 39.7 years and 26.5 kg/m2, respectively. Of all, 62.4%, 55.2%, 52.5%, 52.3%, and 49.2% had unhealthy traits of sleep satisfaction, alertness, sleep regularity, sleep timing, and sleep efficiency, respectively. Obesity in women was associated with unhealthy daytime alertness (Adjusted-OR 1.30, p 0.013), unhealthy sleep regularity (Adjusted-OR 1.23, p 0.016), and surprisingly healthy sleep efficiency (Adjusted-OR 0.80, p 0.019). Obesity in men was associated with unhealthy sleep satisfaction (Adjusted-OR 1.26, p 0.001) and healthy daytime alertness (Adjusted-OR 0.61, p 0.001). In conclusion, sleep regularity, satisfaction, and daytime alertness were associated with obesity, and gender moderated this association. Multiple domains of sleep health could influence maintaining a healthy weight that warrants the attention of public health agendas.